Mechanisms of Scarless Repair at Time of Menstruation: Insights From Mouse Models - Kirkwood, Phoebe M.; Shaw, Isaac W.; Saunders, Philippa T. K. (Frontiers in Reproductive Health, 2022)
The human endometrium is a remarkable tissue which may experience up to 400 cycles of hormone-driven proliferation, differentiation and breakdown during a woman's reproductive lifetime. During menstruation, when the luminal portion of tissue breaks down, it resembles a bloody wound with piecemeal shedding, exposure of underlying stroma and a strong inflammatory reaction. In the absence of pathology within a few days the integrity of the tissue is restored without formation of a scar and the endometrium is able to respond appropriately to subsequent endocrine signals in preparation for establishment of pregnancy if fertilization occurs. Understanding mechanisms regulating scarless repair of the endometrium is important both for design of therapies which can treat conditions where this is aberrant (heavy menstrual bleeding, fibroids, endometriosis, Asherman's syndrome) as well as to provide new information that might allow us to reduce fibrosis and scar formation in other tissues. Menstruation only occurs naturally in species that exhibit spontaneous stromal cell decidualization during the fertile cycle such as primates (including women) and the Spiny mouse. To take advantage of genetic models and detailed time course analysis, mouse models of endometrial shedding/repair involving hormonal manipulation, artificial induction of decidualization and hormone withdrawal have been developed and refined. These models are useful in modeling dynamic changes across the time course of repair and have recapitulated key features of endometrial repair in women including local hypoxia and immune cell recruitment. In this review we will consider the evidence that scarless repair of endometrial tissue involves changes in stromal cell function including mesenchyme to epithelial transition, epithelial cell proliferation and multiple populations of immune cells. Processes contributing to endometrial fibrosis (Asherman's syndrome) as well as scarless repair of other tissues including skin and oral mucosa are compared to that of menstrual repair.